ROBUSTNESS ANALYSIS OF VARIOUS CONFIGURATIONS OF STEEL STRUCTURE UNDER CORROSION IN THE FUNCTION OF TIME - RAHMAWATI (NIM : 25014025), AULIA
Steel structure is commonly used for construction building either for Ordinary Moment Resisting Frame (OMF), Intermediate Moment Resisting Frame (IMF), or Special Moment Resisting Frame (SMF). For steel structures, the identification of failures in the service life is important to be assessed, one of which is the failure due to corrosion. This research will analyze the performance of steel structure under corrosion effect with the function of time. The objects reviewed in this analysis are the Ordinary Moment Resisting Frame (OMF), Intermediate Moment Frame (IMF), and Special Moment Resisting Frame (SMF) which will be designed according to the SNI (IndonesiaÃ‚Â’s Design Code). Those structures will be designed in the same condition. The parameters to be assessed through this analysis are collapse load, safety factor, robustness factor, and redundancy factor, which will be known through pushover analysis using ETABS. The analysis result shows the greatest collapse load among those structures is given by IMF structure. Meanwhile, based on analysis using ETABS, the SMF structure provides the greatest safety factor. However, all of configurations in this analysis are not providing a good result of robustness factor. For the redundancy factor, the result shows that all of configuration are capable to be burdened after the local failure has been reached. By using corrosion as the damage scenario, OMF structure gives the greatest value of redundancy factor.